1990
DOI: 10.1007/bf01963643
|View full text |Cite
|
Sign up to set email alerts
|

Failure of teicoplanin therapy in two neutropenic patients with staphylococcal septicemia who recovered after administration of vancomycin

Abstract: A report is given on two neutropenic patients with staphylococcal septicemia caused by Staphylococcus haemolyticus and Staphylococcus aureus (both strains methicillin-resistant) who failed to respond to therapy with teicoplanin. Both strains were resistant to teicoplanin (MIC 16 and 8 mg/l respectively), but remained sensitive to vancomycin (MIC 2 and 4 mg/l respectively). Replacement of teicoplanin with vancomycin led to full recovery of both patients and their discharge from hospital. These two cases emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 14 publications
1
27
1
1
Order By: Relevance
“…Similarly to observations described for some laboratory or clinical isolates of moderately glycopeptide-resistant mutants of various coagulase-negative staphylococci and S. aureus (6,(22)(23)(24)(25)34), the highly vancomycin-resistant mutant of S. aureus, VM, also showed changes in several protein bands when analyzed by SDS-PAGE. Some of these proteins showed increased amounts in the mutant (e.g., two proteins with the highest molecular masses of 130 and 110 kDa and the proteins in the molecular mass range of 31.5, 29, 21, 18, and 17.5 kDa), while some others appeared to have decreased representation FIG.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similarly to observations described for some laboratory or clinical isolates of moderately glycopeptide-resistant mutants of various coagulase-negative staphylococci and S. aureus (6,(22)(23)(24)(25)34), the highly vancomycin-resistant mutant of S. aureus, VM, also showed changes in several protein bands when analyzed by SDS-PAGE. Some of these proteins showed increased amounts in the mutant (e.g., two proteins with the highest molecular masses of 130 and 110 kDa and the proteins in the molecular mass range of 31.5, 29, 21, 18, and 17.5 kDa), while some others appeared to have decreased representation FIG.…”
Section: Discussionsupporting
confidence: 71%
“…While current concern is directed primarily to interspecific transfer of enterococcal resistance genes, attention has also been paid to other, alternative vancomycin resistance mechanisms that may emerge among S. aureus and coagulase-negative strains of nosocomial staphylococci as a consequence of the extensive use of vancomycin in the hospital environment worldwide (for a review, see reference 42). Moderately increased vancomycin (and teicoplanin) MICs have indeed been noted among some clinical isolates of coagulase-negative staphylococci (3,6,20,31,32,40), and glycopeptide-resistant variants or mutants of staphylococci have also been isolated in several laboratories by the usual step-pressure procedures (5,7,8,16,18,40).…”
mentioning
confidence: 99%
“…However, the cutoff value of teicoplanin of 12 mg/liter was not sensitive enough for the detection of hVISA in China. It has been reported that a strain of MRSA might become heterogeneously resistant to teicoplanin before it becomes heterogeneously resistant to vancomycin (2,18), a phenomenon that requires further investigation. The points summarized above refer to surveillance studies aimed at measuring or estimating the prevalence rates of hVISA among large numbers of isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Both the terms glycopeptide-intermediate S. aureus (GISA) and vancomycin-intermediate S. aureus (VISA) have been used in the literature and in essence are interchangeable. However, it is clear that reduced teicoplanin susceptibility can be present in S. aureus without a clearly demonstrated reduction in vancomycin susceptibility (34,113), whereas generally, VISA strains have demonstrated reduced teicoplanin susceptibility (183). Because the majority of in vitro susceptibility testing uses vancomycin, and much of the literature uses the term vancomycin-intermediate S. aureus (VISA) and heterogeneous VISA (hVISA), this review will use this terminology.…”
Section: Introductionmentioning
confidence: 99%